Pemasangan Tulisan Stainless Steel sebagai Identitas Perumahan-Kawasan - Syamsul Hadi; Bambang Irawan; Purwoko Purwoko; Haris Puspito Buwono; Anggit Murdani (LPPM UNINUS, 2021)
Confusion of guests/address seekers is a problem they face because of the same 3 housing names, namely Puri Kartika Asri (in Tasikmadu; Jl. Raden Panji Suroso, Blimbing, Malang; and Arjowinangun, Kedungkandang, Malang), but different locations accompanied by 4 developer names are the same, namely Puskopad (Tasikmadu; Jl. Panglima Sudirman; Jl. Sulfat area; and Jl. Mayjen Sungkono, Singosari Malang). The purpose of installing writing is to help guests or grab/gojek drivers or address or postal/delivery service companies for letters/documents/goods/entrusted or guests to a Multipurpose Building in a residential area. The writing method includes deliberations with residents to determine the design of the letter model for the construction of the pergola (where the vines grow) in the form of a gate at the housing gate, ordering letters from stainless steel, embossed type that is rust/weather resistant and roofing bolts to tie letters on the frame, construction that is linked to the framework of the pergola, assessment of robustness and authenticity of placement, adjustment of position, and submission to the Head of RT where the address is posted. The results of the installation of writing in the form of displaying a clear address which implies that there is no more confusion for guests/address seekers to meet those they are addressed to with the conclusion that the address writing clearly acts as a housing-area identity, resulting in synergy between State Polytechnic of Malang and the community in obtaining the benefits of assistance and beauty at RT 01-03 at RW 06 Tasikmadu, Lowokwaru, Malang.